2015
DOI: 10.1039/c4ra14090g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a transparent amorphous cellulose film

Abstract: Amorphous cellulose film (ACF) was prepared from cellulose solution in lithium chloride (8 wt%)/N,Ndimethylacetamide by regeneration with acetone. The obtained ACF possessed a dense, smooth surface, and excellent transparency. The X-ray diffraction results indicated that ACF was highly amorphous, which was further confirmed by solid-state 13 C-NMR and Fourier transform infrared (FT-IR) spectra. The tensile analysis implied that the elongation at break (23.9%) and the maximum stress (157 MPa) of ACF derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 48 publications
8
36
0
Order By: Relevance
“…[30,31] In addition, absorbance at 3340 cm À1 in the native BC was blue shifted to 3354 cm À1 accompanied by broadening, in accordance with the previous observations. [8] In the cases for I β rich plant celluloses, similar shift was observed in the higher wavenumber region from 3352 to 3472 cm À1 . [31] In this region, stretching vibrations because of free OH (3458 cm À1 ), hydrogen bonded C 3 OH (3336 cm À1 ), and hydrogen bonded C 2 OH (3267 cm À1 )…”
supporting
confidence: 71%
See 1 more Smart Citation
“…[30,31] In addition, absorbance at 3340 cm À1 in the native BC was blue shifted to 3354 cm À1 accompanied by broadening, in accordance with the previous observations. [8] In the cases for I β rich plant celluloses, similar shift was observed in the higher wavenumber region from 3352 to 3472 cm À1 . [31] In this region, stretching vibrations because of free OH (3458 cm À1 ), hydrogen bonded C 3 OH (3336 cm À1 ), and hydrogen bonded C 2 OH (3267 cm À1 )…”
supporting
confidence: 71%
“…[7] Recently, Zhang et al developed a method for preparation of amorphous cellulose films with excellent transparency from dimethylacetamide (DMAc)-lithium chloride (LiCl) solutions by using acetone as the regeneration solvent. [8] Although applicability of this method to BC is briefly mentioned in this report, no detailed description was explained by using the BC sheets usually prepared in Southeastern Asia countries including Indonesia. Matsumoto et al also reported that the solution of BC in the DMAc-LiCl exhibits optical anisotropy and has a different viscosity behavior from plant origin celluloses, [9] but did not refer to the film formation.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller quantities are converted into a wide variety of derivative products such as cellophane and rayon [1,2]. Conversion of cellulose from energy crops into biofuels such as cellulosic ethanol is under investigation as an alternative fuel source [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…vii) It has excellent optical transparency-comparable to glass and most plastics -over the entire visible range, as well as in the UV range. 16 Paper microfluidic systems 4,17 are based on the spontaneous wicking of liquids (especially water and aqueous buffers) through the porous matrix of cellulose-based paper, often through a fluid path defined by hydrophobic wax barriers. 18 Widely used analytical methodologies such as electrochemical monitoring of glucose, and lateral flow immunoassays were the first (and still largest volume) paper-based devices to enter large-scale fabrication (unless we count simple sensing paper strips).…”
Section: Introductionmentioning
confidence: 99%